2022
DOI: 10.1007/s10493-022-00715-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profile of the predatory mite Amblyseius swirskii (Acari: Phytoseiidae) on different host plants

Abstract: Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) is a predatory mite, effective at controlling whiteflies and thrips in protected crops. However, on tomato its efficacy as a biocontrol agent is hindered, most probably by the plant trichomes and their exudates. Our aim was to characterize the response of A. swirskii to the tomato trichome exudates and identify three major detoxification gene sets in this species: cytochromes P450 (CYPs), glutathione S-transferases (GSTs) and carboxyl/cholinesterases (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The literature on NO-dependent responses of plants infested with arachnids is extremely limited [175,244]. In plants infested with arachnids, the involvement of ROS metabolism [245][246][247], antioxidant enzymes [246,248], phytohormone interactions [249,250], and transcriptomic [251,252] and proteomic changes [253] have been studied. Nevertheless, despite the proven strong links between NO and the response to biotic stresses, there is no direct evidence in the literature.…”
Section: Arachnidsmentioning
confidence: 99%
“…The literature on NO-dependent responses of plants infested with arachnids is extremely limited [175,244]. In plants infested with arachnids, the involvement of ROS metabolism [245][246][247], antioxidant enzymes [246,248], phytohormone interactions [249,250], and transcriptomic [251,252] and proteomic changes [253] have been studied. Nevertheless, despite the proven strong links between NO and the response to biotic stresses, there is no direct evidence in the literature.…”
Section: Arachnidsmentioning
confidence: 99%
“…Exploratory transcriptomic analyses of predators on different host plants revealed that the generalist predatory mite Amblyseius swirskii does not differentially express classical detoxification and transporter genes after short-time exposure to tomato plants, suggesting that in Phytoseiidae predators, detoxification may not play an important role in host plant adaptation. 26 The current study uses the P. persimilis-T. urticae predator-prey system to investigate how BCAs adapt to challenging host plants by performing experimental evolution under controlled laboratory conditions. In a replicated experimental setup, we transferred a P. persimilis population to bean, tomato and cucumber plants for at least 12 generations and tested whether adaptation occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the molecular–genetic changes associated with plant and prey adaptation in P. persimilis are unknown. Exploratory transcriptomic analyses of predators on different host plants revealed that the generalist predatory mite Amblyseius swirskii does not differentially express classical detoxification and transporter genes after short‐time exposure to tomato plants, suggesting that in Phytoseiidae predators, detoxification may not play an important role in host plant adaptation 26 …”
Section: Introductionmentioning
confidence: 99%
“…Tomato plants are covered with trichomes. These protect the plants from a range of herbivores but also hamper or kill natural enemies, including phytoseiid predators (Kant et al 2015;Paspati et al 2021;Paspati et al 2022;van Houten et al 2013).…”
Section: Introductionmentioning
confidence: 99%